DOCUMENT INFORMATION SYSTEM OF EXPORT GOODS AT THE PROVINCE OF INDUSTRY AND TRADE DEPARTMENT WEB-BASED NORTH SUMATRA - Endra A. P. Marpaung (Sean Institute, 2021)
Documents are the most important part of an agency, both government agencies and self-supporting companies. Operational activities carried out in agencies or companies will be recorded in a document or file for distribution to certain parties so that the information contained in the document can be conveyed. Delays and inaccuracies in the data or information provided can occur because the procedures for making documents and information are not systematic or computerized. Avoiding errors in a document can be overcome by the presence of a system or application. So with that an agency or company needs to provide or prepare a system or application to deal with problems as described above. This study discusses how to build an application that can be used by a company or agency in order to avoid the distribution of document information on export goods. The application to be built uses the PHP programming language, which is a Web-based application